CRIMINAL LAW POLICY CONCERNING PROVIDING RESTITUTION TO VICTIMS OF CRIMES OF SERIOUS PERSECUTION - S. Siagian, Fahrizal; Mulyadi, Mahmud; Rosmalinda, Rosmalinda (Semarang Law Review (SLR), 2024)
The crime of serious maltreatment is a form of physical abuse. Therefore, everyone has the right to apply for restitution. Lack of support from various elements makes this condition an obstacle experienced by law enforcement officials in the implementation of restitution for victims of serious maltreatment. There is no provision to force perpetrators of serious maltreatment to pay restitution decided by the court. This is an obstacle in the implementation of restitution in the Indonesian criminal justice system. The problems of this research are How is the Position of Restitution for Victims of Crime in the Indonesian Criminal Justice System? How is the Implementation of Restitution towards the Fulfilment of the Rights of Victims of Serious Offences? What is the Criminal Law Policy on the Provision of Restitution to Victims of Serious Offences in the Indonesian Criminal Justice System in the Future? The purpose of the research is to answer several problems in this study. This research uses normative juridical method with case, concept, and legislation approach. This research obtained results in the form of the Position of Restitution for Victims of Crime in the Criminal Justice System in Indonesia has not been perfectly regulated so that it is considered not to accommodate justice for victims. Implementation of Restitution for Victims of Serious Offences has not been maximised, marked by many technical and non-technical obstacles that hinder restitution. Criminal Law Policy related to restitution for victims in the future is to formulate a policy so that restitution has the intensity of an obligation for the perpetrator to pay it and there must be an institution that pro-actively supervises the provision of restitution. The research initiated a reformulation of legal substance related to strengthening the essence of coercion and strict supervision in the provision of restitution to victims of serious maltreatment in the criminal justice system in Indonesia.AbstrakTindak pidana penganiayaan berat merupakan penyiksaan terhadap fisik manusia. Sehingga setiap orang berhak untuk mengajukan hak restitusi. Kurangnya dukungan dari berbagai elemen sehingga kondisi ini menjadi kendala yang dialami oleh aparat penegak hukum dalam implementasi restitusi bagi korban tindak pidana penganiayaan berat. Belum diaturnya upaya paksa bagi pelaku tindak pidana penganiayaan berat untuk membayar restitusi yang diputus di Pengadilan. Hal ini menjadi sebuah kendala dalam penerapan restitusi dalam sistem peradilan pidana Indonesia. Permasalahan penelitian ini yaitu Bagaimana Kedudukan Restitusi Terhadap Korban Tindak Pidana di dalam Sistem Peradilan Pidana di Indonesia ? Bagaimana Implementasi Pemberian Restitusi Terhadap Pemenuhan Hak-hak Korban Tindak Pidana Penganiayaan Berat ? Bagaimana Kebijakan Hukum Pidana Tentang Pemberian Restitusi Terhadap Korban Tindak Pidana Penganiayaan Berat dalam Sistem Peradilan Pidana Indonesia pada Masa yang Akan Datang ? Tujuan penelitian yakni menjawab beberapa permasalahan pada penelitian ini. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan kasus, konsep, dan perundang-undangan. Penelitian ini memperoleh hasil berupa Kedudukan Restitusi Terhadap Korban Tindak Pidana di dalam Sistem Peradilan Pidana di Indonesia belum sempurna diatur sehingga dinilai belum mengakomodir keadilan terhadap korban. Implementasi Pemberian Restitusi Terhadap Korban Tindak Pidana Penganiayaan Berat belum maksimal yang ditandai dengan banyaknya kendala teknis maupun non-teknis yang menghambat restitusi. Kebijakan Hukum Pidana terkait restitusi bagi korban kedepannya adalah dengan memformulasi suatu kebijakan agar restitusi memiliki intensitas kewajiban bagi pelaku untuk membayarnya serta harus ada lembaga yang pro-aktif mengawasi pemberian restitusi ini. Penelitian menggagas adanya reformulasi substansi hukum terkait penguatan esensi upaya paksa dan pengawasan ketat dalam pemberian restitusi terhadap korban tindak pidana penganiayaan berat dalam sistem peradilan pidana di Indonesia.